Livelihood assessment in district 1 of Medellin - Colombia (2015)
The livelihood approach aims at the analysis, understanding and restrictions that the poorest people have to face in order to recover from difficult situations. The Department for International Development model is applied to an urban zone with the purpose of making an assessment of the livelihood of the district 'la Comuna 1' in Medellin, Colombia, which has been recognised as the poorest and one of the most dangerous districts of the city. The case study presents both a quantitative analysis (macro) and qualitative (micro) analysis, as a mixed method that allows a more complete analysis and understanding of livelihood, and providing a deeper understanding of the district from the livelihood approach. The results indicate a stable growth of livelihood during the period of analysis. © 2015 Ciro Alfonso Serna Mendoza et al., published by De Gruyter Open.